Autoridade e formação: relações sociais na sala de aula e no recreio - Casco, Ricardo (2007)
Taking the theoretical production of T. W. Adorno, M. Horkheimer and H. Marcuse as main reference, this study has privileged the comprehension of different types of teaching authority practice and its possible associations with social relationships established among students in the classroom and at playtime. An empirical research based on the observation of social relationships that occurred inside a group of students from the 4th grade of a municipal public elementary school, in São Paulo, was accomplished in 2005. The observations in the classroom fell upon the frequency of aggressions and reprehensions among students, their participation in school s activities, as well as teachers reprehensions and praises. Some observations that let us analyze the students insertions in social groups organized at playtime, as well as the activities that they developed, were accomplished too. After comparing and analyzing the two sets of data (especially through tables, sociograms and statistic tests), we could realize some associations between the teacher s authority practice and the social relations constituted among students. During the study we noticed that the students who were reprehended by the teacher because they couldn t perform their school tasks were the same that were reprehended by their peers in the classroom for the same reasons, just as these students also had difficulties of being inserted in social groups formed during playtime. At playtime, students who were beaten in the classroom did not take part in groups of their own class; those who were praised by the teachers preferred ludic activities and took part in solid groups; those who reprehended and beat their classmates occupied the central space at playtime with vigorous sports; the participative students constituted solid groups. The researches that focus the relations between what happens in the classroom and the social relationships constituted by students during playtime establish a rich perspective still not so much explored of studies that aim to enlarge the comprehension about school and social processes that act upon the individual development